Un "selfie" in dialisi: valutazione delle abitudini personali degli infermieri di un centro dialisi - Alessandro Capitanini (AboutScience Srl, 2021)
Introduction: Healthcare workers represent a population that is well analysed by health studies: since 1976, the Nurses' Health Study has been examining American nurses for health-related risks and is currently recruiting its third cohort. The survey models used are predominantly biomedical, i.e. based on the disease-healing scheme which focuses on purely biological factors with little or no assessment of psychological, behavioural and environmental aspects. The biopsychosocial assessment model, in its multifaceted nature, is probably more suitable for assessing occupational distress as a progressive cause of health worker burnout. It attributes the outcome of illness, as well as that of health, to the numerous, complex interactions of biological, psychological and social factors. In this work, we decided to evaluate the lifestyle and habits of a homogeneous population of nurses, all belonging to an Operative Unit of Nephrology (Pistoia). Methods: We decided to use unconventional instruments: a "selfie" questionnaire on habits, constructed with scientifically validated items, aimed at the self-assessment of habits, scientifically recognised as determinants of health (nutritional, behavioural, relational, physiological...), correlating it with the analysis of the receipts of the weekly shopping of the family unit of the nurse in the study, according to the principle that "we eat what we buy". Results and conclusion: Nurses evaluated in the study showed a frequent unhealthy lifestyle which can have negative effects on their health, on their family and, consequently, on their work environment. Questionnaire and focus group discussions were appreciated and potentially useful and effective in changing bad habits.